DEVELOPMENT OF TORT LIABILITY FOR INJURY TO THE UNBORN - Tsintsadze, Ketevan (European Scientific Journal, ESJ, 2014)
Both the common law and the law of civilian jurisdictions recognize an unborn child as in esse for purposes of receiving certain civil rights. In most of the cases involving prenatal injuries, it has been advocated that the tort law, by analogy to criminal law and property law, should recognize an unborn child as a person in being. The courts formerly rejected this argument, saying that in order to protect social and property interests a "fiction" has arisen that an unborn child is in being but that this "fiction" should not be invoked to protect personal security. The recent cases have found the protection of an unborn child’s personal security to be equally important as the protection of social and property interests, but have impliedly limited the protection to the personal interests of a viable child. The object and purpose of this article is to analyze and review development of tort liability for injury to the unborn - from the first precedential case till the newest era of liability for prenatal injuries, especially in those conditions, when Georgian Civil Legislation does not recognize this type of Tort Liability.